CHRONIC MOTOR-NEURON DISEASE POSSIBLY RELATED TO INTOXICATION WITH ORGANOCHLORINE INSECTICIDES - Fonseca, Ronaldo Guimarães [UNESP]; Resende, LAL; Silva, M. D.; Camargo, A. (Munksgaard Int Publ Ltd, 1993)
We report on two patients with a history of chronic exposure to organochlorine insecticides who developed clinical and electromyographic signs and symptoms of chronic motor neuron disease. Measurements of aldrin, lindane and heptachlor confirmed the intoxication. We emphasize the importance of searching for toxic and environmental factors in cases of motor neuron disease especially in Third World countries, where workers usually wear no adequate protective equipment.